Galactosyl carbohydrate residues on hematopoietic stem/progenitor cells are essential for homing and engraftment to the bone marrow - Takagaki, Soichiro (Sci Rep, 2019)
The role of carbohydrate chains in leukocyte migration to inflamed sites during inflammation and trafficking to the lymph nodes under physiological conditions has been extensively characterized. Here, we report that carbohydrate chains also mediate the homing and engraftment of hematopoietic stem/progenitor cells (HSPCs) to the bone marrow (BM). In particular, we found that transplanted BM cells deficient in β-1,4-galactosyltransferase-1 (β4GalT-1) could not support survival in mice exposed to a lethal dose of irradiation. BM cells obtained from mice deficient in β4GalT-1 showed normal colony-forming activity and hematopoietic stem cell numbers. However, colony-forming cells were markedly rare in the BM of recipient mice 24 h after transplantation of β4GalT-1-deficient BM cells, suggesting that β4GalT-1 deficiency severely impairs homing. Similarly, BM cells with a point mutation in the UDP-N-acetylglucosamine 2-epimerase/N-acetylmannosamine kinase gene, encoding a key enzyme in sialic acid biosynthesis, showed mildly impaired homing and engraftment abilities. These results imply that the galactosyl, but not sialyl residues in glycoproteins, are essential for the homing and engraftment of HSPCs to the BM. These findings suggest the possibility of modifying carbohydrate structures on the surface of HSPCs to improve their homing and engraftment to the BM in clinical application.